Ivermectin resistence of three Rhipicephalus microplus populations using the larval immersion test - Villar, David; Puerta, Jonathan; López, Anderson; Chaparro, Jenny J (Revista Colombiana de Ciencias Pecuarias, 2016)
in Colombia, the control of tick infestation in cattle is almost exclusively performed with chemical acaricides. It is important to determine the degree of resistance of Riphicephalus microplus field populations to ivermectins (IVM) as the first step to design strategies to increase the useful life of acaricides and decrease the reliance on chemical controls. Objective: to test the degree of resistance to IVM. Methods: three cattle farms in Antioquia (Colombia) where IVM had previously failed to control infestations of R. microplus ticks were studied. Ticks were collected several months apart in 2013, and the larval immersiontest (LIT) was performed on the progeny of the adult females. Concentration-mortality data were subjected to probit analysis. Results: the three populations showed lethal concentrations (LC) 50 and 99 of ≥ 30 ppm and ≥ 400 ppm, respectively. There was no difference observed in the LC at different times of collection for each population studied. Such high values for LC, together with very low regression slopes (≤ 2), indicated a very heterogeneous response to increasing concentrations of IVM, which is common for resistant populations. At two farms, subcutaneous injection with a long-acting formulation of IVM at a dosage of 630 μg/Kg was ineffective at eliminating existing infestations and protecting against reinfestations, confirming farmer suspicions of lost efficacy. Conclusion: epidemiological studies are necessary to assess the current status of resistance to IVM in this region of Colombia, and it is likely that the intensive use of IVM will aggravate this situation in the future.